Influence Of Glycerin On Energy Properties O Fuel Pellets From Oil Palm Fronds Of Agricultural Residues - Muhamed Sharizal Sirrajudin; Mohd Sukhairi Mat Rasat; Razak Wahab; Mohd Hazim Mohamad Amini; Mohamad Azhar Ibrahim; Puad Elham (2016)
Biomass from agricultural residue is an important source for renewable energy. Oil palm frond is one of the abundantly agricultural waste available from oil palm plantation area in Malaysia. Processing the oil palm fronds into fuel pellets are seen as attractive option, which is expected to reduce the amount of agricultural waste in plantation area. The present study investigate the influence of oil palm fronds on pelletizing and combination with glycerin, a by-product from biodiesel production on energy production. The glycerin was combined with oil palm fronds as a biomass binder to enhance the properties with optimum ratio of ingredients (ratio of raw material and glycerin) for producing fuel pellets. The glycerin content ranging from 15 to 45% (by weight), enhanced the calorific value of the oil palm fronds from 16.25 MJ/kg to 17.02 – 22.72 MJ/kg. The results from the proximate and energy content analyses met pellet fuel standard requirement according to Pellet Fuel Institute (PFI). The highest of 22.72 MJ/kg heating value of fuel pellet were achieved from middle portion of 1.5 mm particle size with the mixture ratio was 55:45; oil palm frond and glycerin respectively. From the result, the combination of oil palm fronds and glycerin can be used as an alternative material for biomass energy sources